2020
DOI: 10.1016/j.energy.2020.117280
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies of a fatty acid based phase change dispersion for enhancing cooling of high voltage electrical devices

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Differential scanning calorimetry (DSC) and T-history analyses showed that the apparent specific heat capacity of the sample doubled that of water at around 323 K [18]. The heat transfer performance of that same emulsion and its potential for advanced temperature management in high voltage electrical devices was experimentally and numerically evaluated in two recent works from the same authors [19,20]. When it comes to fatty alcohols such as 1-hexadecanol (also known as cetyl or palmityl alcohol), these materials have proved effective as core for the preparation of micro- [21][22][23][24][25] or nano-encapsulated [26] PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) and T-history analyses showed that the apparent specific heat capacity of the sample doubled that of water at around 323 K [18]. The heat transfer performance of that same emulsion and its potential for advanced temperature management in high voltage electrical devices was experimentally and numerically evaluated in two recent works from the same authors [19,20]. When it comes to fatty alcohols such as 1-hexadecanol (also known as cetyl or palmityl alcohol), these materials have proved effective as core for the preparation of micro- [21][22][23][24][25] or nano-encapsulated [26] PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…The PCD developed for this investigation was formulated with a specific application in mind-for the temperature-sensitive electronic cooling of high-voltage direct-current (HVDC) converter components at 50°C. Within high power transmission systems and devices such as HVDC converters, issues arise with thermal management, as within these systems, there is a high power dissipation, which can be up to 30% of the total HVDC power loss [13]. Not only does this cause problems with thermal runaway in the system, but the power losses resulting from the high power dissipation result in large maintenance costs for the operating plants [14,15].…”
Section: Envisioned Applicationmentioning
confidence: 99%
“…Air cooling, which is used through either forced or natural flux through cooling air channels, is normally used for electronic devices with power dissipation rates below 1500 W [14,16]. However, in the case of HVDC, this value can be up to 10 kW, and for this, air is not sufficient [13,14,17]. Water has a high cooling efficiency; however, only sensible heat can be exploited [16], as the cooling of HVDC converters is required at 50 degrees.…”
Section: Envisioned Applicationmentioning
confidence: 99%
“…Many of them are for cooling or air-conditioning purposes. 2,3,5,9,10 However, there is a significant dearth in the literature of PCDs operating at temperatures below 0 °C. To make use of such PCDs, the continuous phase (usually water) must be modified.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in many applications, cold has to be supplied at the “best temperature”. One reason can be to keep the device being cooled isothermal for reasons like the precision of machine spindles or high-voltage thyristor cooling. , Another reason is the prevention of damage to the product if the temperatures are too low or too high.…”
Section: Introductionmentioning
confidence: 99%